Emigration from Croatia to Canada based on a woman's narrative - Rajković Iveta, Marijeta (2011)
A presentation provides a case study of trans-continental emigration through a story of a woman who emigrated from one Croatian village to Toronto (Canada). Position of a woman within the family and a local community in her birthplace, in the private and public sphere, reveals that gender roles were given at birth and also implies to sexual symbolism in the first half of the 20th century. When her husband left for Canada she stayed for some time in her birth place as a housewife within his numerous family. After making their final decision to move to Canada for good, she went there too. There is a comparative observation of the changes in her life upon her arrival in a big city where she lived in a nuclear family and became a worker. Her destiny, subjective and emotional experience of migration will be exemplified by interviews, family photos, letters and documents. During the 1990s she retired and came back to Croatia because she was home sick. The research of migrations proves that women were not in a focus of interest and that they were simply regarded as dependent and passive companions of male migrants. This presentation will contribute to better understanding of female perception of relocating and return.